Autoerythrocyte sensitization (Gardner-Diamond syndrome) in men: a case report and review of the literature. Issue 719 (September 1985) - Ingber, A.; Alcalay, J.; Feuerman, E. J.
Abstract : Autoerythrocyte sensitization (AES) is a rare syndrome particularly among males. A young male with typical AES is herewith described. We review all seven published cases of AES in men for which details are available and compare the age of onset, somatic manifestations, associated diseases and psychiatric disturbances between the sexes. We emphasize that the criteria essential for a diagnosis of AES should include typical clinical presentation, longstanding clinical history and a positive skin test with the patient's blood. Because of the rarity of AES there is a lack of awareness regarding it among many doctors.